Pelas lentes do miriti: um olhar sobre a cibercultura e a interdisciplinaridade na licenciatura integrada - NUNES, Wykli da Costa (2020)
This study is motivated by the premise of the search for understanding the links between literacy and digital literacy, and the implications and considerations regarding digital culture, cyberculture, taken by undergraduate students in Integrated Degree in Science, Mathematics and Language Education, from the Federal University of Pará, which has an interdisciplinary perspective in its Pedagogical Political Project. The research was developed with a night shift class of the aforementioned course, during the year 2017, using three research instruments: Participant observation; Semi-structured questionnaire and a Research-training, elaborated in audiovisual resource. The analysis of the research turned to the lived experience and the contributions to the questionnaire and the video-research, perceiving the way they are seen in this digital culture, in the light of Pierre Lévy (1999) and his contributions on cyberculture. With this research, it was possible to make some notes about the course and this digital link, such as: 1) The course, despite having an interdisciplinary and integrated view, considers technology only a teaching tool, restricting its real potential; 2) Research participants assume the importance of technology in the classroom, however, do not feel prepared for such a task; 3) The students have many difficulties in dealing with this culture, even being part of it.